A Neurologist’s Guide to Acute Migraine Therapy in the Emergency Room - Gelfand, Amy A. (SAGE Publications, 2012)
Migraine is a common reason for visits to the emergency room. Attacks that lead patients to come to the emergency room are often more severe, refractory to home rescue medication, and have been going on for longer. All of these features make these attacks more challenging to treat. The purpose of this article is to review available evidence pertinent to the treatment of acute migraine in adults in the emergency department setting in order to provide neurologists with a rational approach to management. Drug classes and agents reviewed include opioids, dopamine receptor antagonists, triptans, nonsteroidal anti-inflammatory drugs, corticosteroids, and sodium valproate.